2022
DOI: 10.1093/bjsopen/zrac131
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein embolization versus dual vein embolization for management of the future liver remnant in patients undergoing major hepatectomy: meta-analysis

Abstract: Background This meta-analysis aimed to compare progression to surgery, extent of liver hypertrophy, and postoperative outcomes in patients planned for major hepatectomy following either portal vein embolization (PVE) or dual vein embolization (DVE) for management of an inadequate future liver remnant (FLR). Methods An electronic search was performed of MEDLINE, Embase, and PubMed databases using both medical subject headings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The recent retrospective observational DRAGON 0 study demonstrated a substantially increased resection rate, comparable to that of ALPPS, after PVE/HVE, with a safety profile similar to that of PVE alone 17 . These findings were confirmed in a meta-analysis of all published comparative studies comparing PVE/HVE versus PVE alone, and fit well in the contemporary development of minimization of the physical impact of oncological treatments 18 , 19 . It has not yet been determined whether this also translates into better oncological outcomes.…”
Section: Introductionsupporting
confidence: 72%
“…The recent retrospective observational DRAGON 0 study demonstrated a substantially increased resection rate, comparable to that of ALPPS, after PVE/HVE, with a safety profile similar to that of PVE alone 17 . These findings were confirmed in a meta-analysis of all published comparative studies comparing PVE/HVE versus PVE alone, and fit well in the contemporary development of minimization of the physical impact of oncological treatments 18 , 19 . It has not yet been determined whether this also translates into better oncological outcomes.…”
Section: Introductionsupporting
confidence: 72%
“…Sequential or simultaneous TACE and PVE could help control the tumor progression and further facilitate FLR regeneration, but they did not substantially reduce the long waiting period for staged hepatectomy ( 9 ). A combination of PVE and hepatic vein embolization (HVE) significantly shortened the waiting period to 3–4 weeks and tended to be safe and effective ( 10 ). ALPPS induces the most rapid hypertrophy of FLR and confers a higher rate of earlier resection compared with PVE-based treatments above, but it is associated with a high postoperative mortality and complications rate.…”
Section: Discussionmentioning
confidence: 99%
“…Following liver resection rates of major complications appeared lower as did the incidence of PHLF with DVE, 13% versus 22% (p=0.13) although this did not reach statistical significance. Post-operative mortality was also improved following DVE ( 41 ). Whilst several randomized studies are currently in progress comparing PVE to DVE (DRAGON 1 –Training, Accreditation, Implementation and Safety Evaluation of Combined PVE/HVE – ClinicalTrials.gov NCT04272931 and HYPER-LIV01 the outcomes from retrospective studies, and meta-analysis of these, suggests that DVE is associated with improved hypertrophy and perhaps lower complications, particularly PHLF than PVE alone ( 42 ).…”
Section: Methodsmentioning
confidence: 99%